2022
DOI: 10.1177/01926233221129214
|View full text |Cite
|
Sign up to set email alerts
|

Toxicologic Pathology Forum: Opinion on Not Euthanizing Control Animals in the Recovery Phase of Non-Rodent Toxicology Studies

Abstract: Nonclinical toxicology studies that are required to support human clinical trials of new drug candidates are generally conducted in a rodent and a non-rodent species. These studies typically contain a vehicle control group and low, intermediate, and high dose test article groups. In addition, a dosing-free recovery phase is sometimes included to determine reversibility of potential toxicities observed during the dosing phase and may include additional animals in the vehicle control and one or more dose groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…VCG implementation will result in a reduction of animal use complementing other proposed initiatives such not to euthanize recovery control animals and return them to the stock colony at the completion of the recovery phase. 5 Another consideration for use of VCG is a tiered or retrospective approach. In this scenario study findings, such as histopathology, might be interpreted without CCs.…”
Section: Discussion/conclusion/outlookmentioning
confidence: 99%
“…VCG implementation will result in a reduction of animal use complementing other proposed initiatives such not to euthanize recovery control animals and return them to the stock colony at the completion of the recovery phase. 5 Another consideration for use of VCG is a tiered or retrospective approach. In this scenario study findings, such as histopathology, might be interpreted without CCs.…”
Section: Discussion/conclusion/outlookmentioning
confidence: 99%
“…A recent survey across 4 major organizations found that in non-rodent nonclinical toxicology studies where a recovery vehicle control group was included and euthanized at the end of the study, euthanasia of vehicle control recovery animals was not necessary for the interpretation of findings in ∼95% (116/122 studies) dog and ∼91% (109/120 studies) NHP studies. 14 In ∼5% dog and ∼9% of NHP studies where euthanasia of vehicle control recovery animals was considered necessary for study interpretation, it was considered to have no impact on the study/program outcome except where historical control data (HCD) were not robust. The survey results further indicate that not euthanizing the vehicle control animals could have saved around 460 dogs and 428 NHPs over 14 years without compromising the overall conclusions.…”
Section: Non-terminal Controlmentioning
confidence: 99%